Influences on the location of repeating earthquakes determined from a and b value imaging - Masashi Kawamura; Kate Huihsuan Chen (Geophysical Research Letters)
Abstract To explore where earthquakes tend to recur, we statistically investigated repeating earthquake catalogs and background seismicity from different regions (Parkfield, Hayward, Calaveras, and Chihshang Faults). We show that the location of repeating earthquakes can be mapped using the spatial distribution of the seismic a and b values obtained from the background seismicity. Molchan's error diagram statistically confirmed that repeating earthquakes occur within areas with high a values (2.8–3.8) and high b values (0.9–1.1) on both strike‐slip and thrust fault segments. However, no significant association held true for fault segments with more complicated geometry or for wider areas with a complex fault network. The productivity of small earthquakes responsible for high a and b values may thus be the most important factor controlling the location of repeating earthquakes. We inferred that the location of high creep rate in planar/listric fault structures might be indicated by a values of ~3 and b values of ~1.